EQUITY AND THE GLOBAL POLICY ON CLIMATE CHANGE: A LAW AND ECONOMIC PERSPECTIVE - Wibisana, Andri G. (Indonesia Law Review, 2012)
The opponents of the global commitment to reduce greenhouse gases (GHGs) emissions seem to have shifted their arguments from the one emphasing on the issue of uncertainty to the one focusing on the economic burdens disproportionately placed on the current generation in general, and some developed countries in particular. Inevitably, the issue of equity becomes of highly importance in the recent climate policy debates. This paper attempts to analyze the implementation of equity principles, i.e. intergenerational and intragenerational equity, in the global climate policy. In doing so, it will first briefly outline some prominent economic appraisals on the impacts of climate change. Afterwards, some proposals to incorporate equity into the economic appraisals will be analyzed. Emphasizing on the concepts of equity, this paper will finally offer some recommendations for post-Kyoto negotiations.